2018
DOI: 10.3390/su10072170
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Authentic Leadership on Organizational Citizenship Behaviours and the Mediating Role of Corporate Social Responsibility in the Banking Sector of Pakistan

Abstract: This study was designed to examine the effect of authentic leadership on organizational citizenship behaviour (OCB), as well as to examine the mediating mechanism of corporate social responsibility (CSR) on the aforementioned relationship. Using the cross-sectional design method, the data were collected from 395 employees working in the banking sector of Pakistan. Drawing on social exchange theory, it was hypothesized that authentic leadership would positively predict organizational citizenship behaviour. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 57 publications
4
64
0
1
Order By: Relevance
“…Until recently, researchers into CSR had mainly focused on external stakeholders, such as investors and customers [42,43]. Now, attention has shifted decidedly onto employees [12,44,45]. Employees are one of the most important stakeholders in any organization.…”
Section: Ocb: Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, researchers into CSR had mainly focused on external stakeholders, such as investors and customers [42,43]. Now, attention has shifted decidedly onto employees [12,44,45]. Employees are one of the most important stakeholders in any organization.…”
Section: Ocb: Effectsmentioning
confidence: 99%
“…Spector and Che divided the factors into six groups: attitude (e.g., commitment, level of job satisfaction), negative and positive emotions experienced in connection with the work performed, personality (e.g., diligence), the so-called stressors (e.g., conflicts and their role), employee relations with the supervisor, and the perception of procedures [8]. Other authors point to, for example, leadership behavior, loyalty to the leader, authentic leadership, organizational culture, organizational relations, or organizational justice [9][10][11][12]. Therefore, organizational and citizenship behaviors will be influenced by both organizational and leadership factors, as well as those related to employees themselves.…”
Section: Introductionmentioning
confidence: 99%
“…It seems SR can be used to mitigate social and stakeholders' pressures if the organisation finds perceived benefits of reporting. The discussion also highlight the common gap of Pakistani policy as well as business decision makers the importance and potentiality of the SR in the decision making process (Malik and Kanwal 2016;Sharif and Rashid 2014;Mahmood et al 2018;Ehsan et al 2018;Yunis et al 2018;Iqbal et al 2018). Therefore, it is emergence to find the mechanism of how to understand the explicit and implicit cost and benefits of SR to the management and stakeholders.…”
Section: Perceived Benefits Of Reportingmentioning
confidence: 97%
“…When the study considered against the backdrop of the total number of registered companies (around 15000) and especially the total number of listed companies (around 590) this is a very small number and there is a need to investigate the views of main actors involved in SR on the current state of affairs so that some recommendations can be made for further improvement. Recent studies on CSR disclosure focus on listed firms performance; Nazir 2010 investigates CSR disclosure of fertilizer industry; Nazish 2014 explores regulatory importance of CSR disclosure; Malik Iqbal et al 2018 found the mediating role of CSR in the authentic leadership of Pakistani banking sector. This discussion confirms that CSR disclosure is significantly growing in Pakistan.…”
Section: Corporate Sustainability Reporting In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation